2018
DOI: 10.3390/ijerph15040789
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous Health and Human Rights: A Reflection on Law and Culture

Abstract: In Australia, Aboriginal and Torres Strait Islander peoples bear a greater burden of disease and have lower life expectancy than their non-Indigenous counterparts. These combined indicators are evidence of an entrenched health crisis in the Indigenous population that is linked to systemic disadvantage over many decades. In an effort to improve life expectancy and lessen the burden of disease, a number of strategies and national frameworks now embed a human rights-based approach to achieving health equality. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Past learnings indicated that cultural inequality as it existed throughout much of the twentieth century in Australia as a result of the Segregation Policy (p22 [3]) was felt by local Aboriginal people who remember birthing their babies on the verandah of the hospital [31]. Segregation meant that healthcare was delivered on the outside of the health service for Aboriginal people who at that time found solace in their cultural beliefs and their relationship with their ancestral land.…”
Section: Discussionmentioning
confidence: 99%
“…Past learnings indicated that cultural inequality as it existed throughout much of the twentieth century in Australia as a result of the Segregation Policy (p22 [3]) was felt by local Aboriginal people who remember birthing their babies on the verandah of the hospital [31]. Segregation meant that healthcare was delivered on the outside of the health service for Aboriginal people who at that time found solace in their cultural beliefs and their relationship with their ancestral land.…”
Section: Discussionmentioning
confidence: 99%
“…For those who have suffered most from extraction, including indigenous people, solutions must include enfranchisement with settlement of land rights and the provision of culturally appropriate services. 32 …”
Section: Road Aheadmentioning
confidence: 99%
“…To be fair and effective, UHC must include marginalised groups, such as migrants, refugees, indigenous people, and people working in the informal sector. For those who have suffered most from extraction, including indigenous people, solutions must include enfranchisement with settlement of land rights and the provision of culturally appropriate services 32…”
Section: Road Aheadmentioning
confidence: 99%
See 1 more Smart Citation
“…Aboriginal people and Torres Strait Islander people are the First Nations peoples of the lands now known as Australia and represent 3.3% (n≈800 000) of the Australian population. 1 Colonisation has resulted in ongoing devastation, dispossession and oppression 2 for Aboriginal and Torres Strait Islander people, who continue to experience one of the lowest life expectancies of any population in high-income countries and universal health systems. 1 Cardiovascular disease (CVD) remains the highest contributor to the gap in life expectancy.…”
Section: Introductionmentioning
confidence: 99%